Business process modeling: a case study in the steel industry - Silva, Brenda Siqueira da; Rodrigues, Thiago de Almeida; Bastos, Brenda Schulz (Brazilian Journal of Production Engineering, 2024)
The competitiveness in the business environment has driven companies to improve their internal processes in order to achieve greater satisfaction from customers and employees, as exemplified by the commercial processes in the basic industry. In this context, this study aims to analyze the application of process modeling as a tool in the pursuit of continuous improvement and customer satisfaction. Thus, a multinational steel producer seeking to enhance its sales process by implementing a tool called the ’Customer Portal’ was used as a case study. For this purpose, process models were created using the Business Process Model and Notation (BPMN) methodology, along with interviews with employees to understand the impact of the ’Customer Portal’ on the team’s work routine. This demonstrated how process modeling is an important tool in the pursuit of continuous improvement, aiding in the visualization of the business process, identification of opportunities, relationships between activities, and the definition of responsibilities. Additionally, the case study highlighted challenges and opportunities in change management that can help managers improve processes, especially the resistance from employees who did not participate in the tool implementation process.